Adherence of Pasteurella multocida or Bordetella bronchiseptica to the swine nasal epithelial cell in vitro. - Nakai, T (1988)
The interaction of Bordetella bronchiseptica or Pasteurella multocida with swine nasal epithelial cells was studied in vitro. The mean number of B. bronchiseptica organisms adhered per cell was about three times as high as that of P. multocida (P less than 0.01), and the adherence was specifically inhibited by the homologous antiserum prepared with the whole-cell antigen of each bacterium. The poor affinity of P. multocida to the swine nasal mucosa as compared with that of B. bronchiseptica was also demonstrated in the cultured fragments of the nasal mucosa. When observed with a scanning electron microscope, B. bronchiseptica organisms colonized the fragments, whereas few P. multocida organisms adhered. Morphologically, the P. multocida-infected fragments had an essentially normal structure, whereas marked degeneration and marked desquamation of the epithelial cells and severe inflammatory reactions were observed in many areas of the B. bronchiseptica-infected fragments. These morphological observations were consistent with those for the nasal mucosa of P. multocida- or B. bronchiseptica-infected neonatal pigs (T. Nakai, K. Kume, H. Yoshikawa, T. Oyamada, and T. Yoshikawa, Jpn. J. Vet. Sci. 48:693-701, 1986; T. Oyamada, T. Yoshikawa, H. Yoshikawa, M. Shimizu, T. Nakai, and K. Kume, Jpn. J. Vet. Sci. 48:377-387, 1986). Cultured swine nasal fragments, however, were equally injured when they were incubated in a medium containing purified dermonecrotic toxin (DNT) preparations of B. bronchiseptica or P. multocida. Therefore, these DNT preparations can induce morphological damage closely resembling that induced in vivo. Hence, colonization of B. bronchiseptica and production of its DNT on the swine nasal mucosa appear to result in the production of mucosal damage. On the other hand, P. multocida seems to lack the ability to colonize normal swine nasal mucosa, thus resulting in no production or the slight production of DNT to such an extent as to produce mucosal damage. The present data support our previous hypothesis (Nakai et al.; Oyamada et al.) that B. bronchiseptica induces swine atrophic rhinitis, whereas P. multocida does not.